(untitled) (Research, Society and Development, 2020)
The objective of this research was to study the perception of students of subsequent technical education, observing the profile of each student when using a Virtual Learning Environment (VLE). The students were introduced to the digital platform and several study materials and activity proposals were made available for students to interact with the AVA. After the activities were made available for fifteen days, a questionnaire was applied to verify the quantifiers of students’ access to the platform. In addition to their level of familiarity with the use of computers to carry out school activities. The data obtained were tabulated and descriptive statistics techniques applied to obtain average values ​​for each of the monitored variables. Linear correlation studies were applied to the quantitative data. It was observed that the majority of students (60%) have a computer to carry out their school activities and did not have any difficulties regarding the use of the platform. There was also a correlation between the age factor and internet access, pointing to a decrease in the frequency of internet access with increasing age. Another important factor observed was that 88% of students use complementary materials taken from the internet to complement their studies. In this sense, it was evidenced with this study that the use of digital platforms is a tool that can assist students in the teaching-learning process in the form of complementing their studies.